2016
DOI: 10.15255/cabeq.2014.2093
|View full text |Cite
|
Sign up to set email alerts
|

Esterification of Glycerol with Acetic Acid over Highly Active and Stable Alumina-based Catalysts: A Reaction Kinetics Study

Abstract: The catalytic activity of Cu-or Ni monometallic and Cu-Ni bimetallic (Cu/Ni ratio = 3, 1, 0.33) catalysts supported on γ-Al 2 O 3 and SO 4 2-/γ-Al 2 O 3 catalysts were evaluated for esterification of glycerol. The reactions were performed in a batch reactor under reflux at standard reaction conditions: temperature 110 °C, atmospheric pressure, glycerol to acetic acid molar ratio 1:9, and catalyst loading 0.25 g. The best catalytic activity was observed over 2 M SO 4 2-/γ-Al 2 O 3 catalyst, which showed the gly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
38
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 38 publications
5
38
0
5
Order By: Relevance
“…It can be seen that at 5 minutes the conversion reaches 50%, whereas at 10 minutes the conversion can reach about 72%, and it is almost constant at the 20 th minutes. Similar trend was reported by Rane et al (2016). They found that at higher temperature (70, 90, and 110 o C), the ratio of glycerol concentration and the initial concentration also rises from 0.98; 0.6; and 0.1 at 30 minutes, which Signal Initial Retention time corresponded to reaction conversions of 2, 40 and 90%, at 70, 90, and 110 o C, respectively.…”
Section: Resultssupporting
confidence: 85%
See 4 more Smart Citations
“…It can be seen that at 5 minutes the conversion reaches 50%, whereas at 10 minutes the conversion can reach about 72%, and it is almost constant at the 20 th minutes. Similar trend was reported by Rane et al (2016). They found that at higher temperature (70, 90, and 110 o C), the ratio of glycerol concentration and the initial concentration also rises from 0.98; 0.6; and 0.1 at 30 minutes, which Signal Initial Retention time corresponded to reaction conversions of 2, 40 and 90%, at 70, 90, and 110 o C, respectively.…”
Section: Resultssupporting
confidence: 85%
“…The conversion starts to be constant at 60 minutes at 110 o C, When the glycerol is used in excess, the esterification reaction of glycerol with FFA can be assumed to be an irreversible reaction (Freedman et al, 1984). This idea is supported by Narvaez (2007) and Rane et al (2016) who assumed that the value of k for the reverse reaction is assumed as zero when the glycerol is in excess. This esterification reaction used solid catalyst sized less than 840 µm, so that the reaction kinetics can be approached using the pseudohomogeneous model (Joksimovic and Markovic, 2007).…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations